Introducing China The World's Oldest Great Power Charts its Next Comeback - Huisken, Ron (ANU Press, 2010)
China's transformation has been patiently, methodically and very deliberately constructed by a leadership group that has equally carefully protected its monopoly on power. Today's China is proceeding with great seriousness and determination to become a first-rank state with a balanced portfolio of power and no major vulnerabilities. China takes itself very seriously and is inviting the world to overlook the formidable hard power assets it is determined to acquire in favour of simply enjoying the fruits of its market and trusting in the sincerity of its rhetoric on being determined to become a benign and peaceful new-age major power.